WAKAF DAN POLITIK DI TUNISIA - Budi Juliandi (TAHKIM, 2017)
Tunisia State, by many experts is considered the most progressive, liberal and radical from Muslim countries in its concern for the women's rights issues, and its consistency in banning the polygamy (family law). However, the progression of Tunisia in the family law field, it turn out do not accompanied by its progress in the Islamic economics field, especially in development of waqf. In this regard, Tunisia most underdeveloped compared to other Muslim countries in the field of endowments, such as Saudi Arabia, Egypt, Pakistan, Bangladesh, Sri Lanka, Jordan, Brunei, Malaysia, and Indonesia, although about 19th century, the contribution of land endowments of Tunisia in 1883, has ever reached 1/3 of the entire ownership of land. To date, Tunisia have not institutions and laws governing the endowments. The transition government today (2011-2014), just preparing Draft of Law on endowments in November 2013. However, to date the Regional Representative House of Tunisia has not ratified it. Key words: Endowments, law politic, Tunisia